EVALUASI PENYELENGGARAAN BADAN USAHA MILIK DESA (BUMDES) REJO MULYO, DESA GOGIK, KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Adiatma Nugraha; Kismartini Kismartini (Dialogue : Jurnal Ilmu Administrasi Publik, 2019)
All this time the development centered in the city, leading to gaps between villagesand the city's economy. BUMDes become one of the ideas the government to boost thevillage economy. Gogik village which lies at the foot of mount Ungaran, SemarangRegency has the potential of natural recourses and clean water, its potential is not yetmaximally utilized, Encouraged by Desa Lab Site PMD activities, Rejo Mulyo VillageEnterprise was finally established in Gogik Village in 2011 with the hope of its ability toboost the village economic growth by the means of optimally utilizing its potential.Qualitative Descriptive method is used in this research by focusing on: (1) Evaluatingthe performance of BUMDes Rejo Mulyo, Gogik Village, District West Ungaran,Semarang Regency, (2) The supporting and obstacle factors BUMDes Rejo Mulyo, GogikVillage, District West Ungaran, Semarang Regency. The results of this research lead toa conclusion that the establishment of Rejo Mulyo Village Enterprise has alreadyfollowed the valid regulation at that time, But the performance of BUMDes Rejo Mulyois not maximized because it can not support the welfare of the villagers Gogik. One of thesupporting factors of the performance BUMDes Rejo Mulyo is the spirit and willingnessofficials and employees to subserve the Gogik village. One of the obstacles faced, whichis the biggest natural potential that exists in the Gogik village, are waterfalls Semirang itcan not be utilized because the area is occupied in Perhutani area.